Prevalence of elevated microsatellite alterations at selected tetranucleotide repeats in pancreatic ductal adenocarcinoma - Mori, Taiki (PLoS One, 2018)
Pancreatic ductal adenocarcinoma (PDAC) prognosis remains poor even after complete resection owing to no valuable biomarkers for recurrence and chemosensitivity. Tumors not expressing MSH3 show elevated microsatellite alterations at selected tetranucleotide repeats (EMAST). EMAST reportedly occurs in several tumors. In colorectal cancer (CRC), EMAST was reportedly correlated with 5-fluorouracil (5-FU) sensitivity. However, EMAST prevalence in PDAC and its significance as a prognostic biomarker are unknown. This study aimed to investigate EMAST prevalence in PDAC and the associations between EMAST and pathological factors, EMAST and prognosis, and EMAST and MSH3 expression via immunohistochemistry (IHC). We assessed 40 PDAC patients undergoing surgery. Genomic DNA was extracted from tumors and normal tissues. EMAST and microsatellite instability-high (MSI-H) were analyzed using five polymorphic tetranucleotide markers and five mononucleotide markers, respectively. Tumor sections were stained for MSH3, and staining intensity was evaluated via the Histoscore (H-score). Eighteen of 40 (45%) PDAC patients were EMAST-positive; however, none were MSI-H-positive. Clinicopathological characteristics including overall survival (OS) and recurrence-free survival (RFS) were not significantly different between EMAST-positive and EMAST-negative patients (P = 0.45, 0.98 respectively). IHC was performed to evaluate MSH3 protein expression levels for the PDAC tissue specimens. H-scores of EMAST-positive patients ranged from 0 to 300 (median, 40) and those of EMAST-negative patients ranged from 0 to 300 (median, 170). MSH3 protein was not significantly downregulated in EMAST-positive patients (P = 0.07). This study is a preliminary study and the number of cases investigated was small, and thus, study of a larger cohort will reveal the clinical implication of EMAST.